2003
DOI: 10.1038/sj.pcan.4500640
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor regulation of secreted matrix metalloproteinase and plasminogen activators in prostate cancer cells, normal prostate fibroblasts and normal osteoblasts

Abstract: We assessed the relative levels of secreted matrix metalloproteinases (MMPs) and plasminogen activators (PAs) in PC-3 cells, prostate fibroblasts and osteoblasts in the presence and absence of VEGF, TGFb1 and bFGF. Fibroblasts and osteoblasts secreted more MMPs -1 and -2 than did PC-3 cells, while PC-3 s contributed the majority of PAs. MMP-1 expression was downregulated by transforming growth factor b-1 (TGFb1) treatment in prostate fibroblasts and upregulated by basic fibroblast growth factor (bFGF) in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This complex process requires proliferation, migration, and structural modification of endothelial cells, which are regulated by pro-angiogenic factors, such as basic fibroblast growth factor (bFGF) and vascular endothelial growth factor A (VEGFA) ( 3 ). Further, either alone or in combination, these two factors stimulate proteases and plasminogen activators in tumor tissues to degrade the basement membrane, which promotes tumor metastasis and endothelial cells recruitment for neovascularization ( 4 ). In addition, bFGF and VEGFA can synchronize platelet-derived growth factor (PDGF) and its receptor synergistically to facilitate blood vessel formation by modulating their expression and activation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This complex process requires proliferation, migration, and structural modification of endothelial cells, which are regulated by pro-angiogenic factors, such as basic fibroblast growth factor (bFGF) and vascular endothelial growth factor A (VEGFA) ( 3 ). Further, either alone or in combination, these two factors stimulate proteases and plasminogen activators in tumor tissues to degrade the basement membrane, which promotes tumor metastasis and endothelial cells recruitment for neovascularization ( 4 ). In addition, bFGF and VEGFA can synchronize platelet-derived growth factor (PDGF) and its receptor synergistically to facilitate blood vessel formation by modulating their expression and activation ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to control HMFs, treated with HMF cell conditioned media (HMFCM), HMFs treated with 102 cell conditioned media (102CM) exhibited significantly increased levels of several genes that have been previously associated with activated fibroblasts present in inflammatory situations and CAFs: MMP-1, MMP-3, IL-8, and SDF-1 (3, 8, 18, 45, 46) (Figure 2A). Notably, these genes also promote breast cancer invasion and metastasis (13, 36, 43, 47).…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that adding VEGF neutralizing antibody does not play an important role in the cell invasion during hypoxia. However, using conditioned medium from GA treated hypoxic cells 25 led to a significant decrease in cell invasion in comparison to the wells in which HCM was used (19.6072.60, and 73.2078.49 cells per field, respectively). These data suggest that a decrease in HIF1a leads to a decrease in cell invasion.…”
Section: Inhibition Of Hif-1a By Geldanamycin O Alqawi Et Almentioning
confidence: 86%
“…However, they kept their cells in hypoxia for 24 h. Other studies have demonstrated that VEGF can upregulate MMP-9 via its activation of VEGF receptors in different cell lines. 25,41 They showed an increase in VEGF protein due to VEGF cDNA transfection resulted in an increase in MMP-2 protein. So the upregulation of MMP-2 and MMP-9 by hypoxia or VEGF may be cell type specific, and VEGF or hypoxia in DU-145 cells may not regulate MMP-2 and MMP-9.…”
Section: Inhibition Of Hif-1a By Geldanamycinmentioning
confidence: 99%